What justice? whose justice? : fighting for fairness in Latin America - Eckstein, Susan, 1942-; Wickham-Crowley, Timothy P., 1951- (University of California Press, 2003)
Following up on issues raised in 'Power and Popular Protest: Latin American Social Movements', these essays elucidate how conceptions of justice are socially constructed and contested and historically contingent, shaped by people's values and institutionally grounded in real-life experiences.